A Rare Case of Orbital Lymphoma - Muhammad Waseem; Saquib Naeem; M Saleem Bajwa; Farhat Fatima Roomi (Journal of Bahria University Medical and Dental College)
Orbital lymphoma without systemic involvement is rarely seen in ophthalmological practice. We diagnosed one such case in our set-up. An old female presented with diplopia and proptosis right eye. CT-scan revealed an intraorbital mass along the superior orbital wall. MRI orbit showed space occupying lesion involving frontal sinus which was confirmed on histopathological and Immunohistochemical examinations. The histochemical studies confirmed the presence of non-Hodgkin’s lymphoma. This is a rare manifestation of non-Hodgkin’s lymphoma with primary involvement of orbital mass extending into frontal sinus and cranial fossa with no systemic involvement. This case was being reported for general awareness as the tumour is potentially curable